Characterization of the immune regulatory property of CD22+ CD9+ B cells. Issue 3 (7th July 2022) - Yang, Gui; Suo, Limin; Hu, Suqin; Liu, Huazhen; Wang, Xinxin; Xiao, Xiaojun; Liu, Jie; Zeng, Xianhai; Hong, Jingyi; Guan, Li; Xue, Jinmei; Yang, Pingchang
Abstract: Immunodisruptive homeostasis is recognized in allergic disorders. The mechanism of restoration of immunologic homeostasis in the body is not fully understood. Galectin‐9 (Gal9) and CD22 have immune regulatory functions. The goal of this study is to test the role of CD22 + CD9 + B regulatory cells in immune homeostasis the body. A much smaller amount of IL‐10 in B10 cells was detected in patients with allergic rhinitis (AR) in contrast to healthy subjects. The IL‐10 expression levels in B10 cells were positively correlated with the CD22 expression. CD22 mediated the effects of Gal9 on the enhanced expression of IL‐10 in AR B10 cells. Gal9 overcame the refractory induction of IL‐10 in B‐cells of AR subjects. The immune regulatory ability of AR B10 cells could be restored by Gal9. Combination of Gal9 and SIT induced and activated antigen‐specific B10 cells. The B10 cells of Gal9/specific immunotherapy‐treated AR mice showed immunosuppressive functions on T‐cell activities and induction of type 1 regulatory T cells in an antigen‐specific manner. Administration of Gal9 potentiated the effects of specific immunotherapy in mice with AR. In summary, a fraction of regulatory B cells, the CD19 + CD22 + CD9 + B cells, was characterized in the present study. CD22 mediates the effects of Gal9 to promote immunotherapy for allergic diseases by inducing B10 cells. In an antigen‐specific manner, the B10 cells suppressed CD4 + T cell activities, and alleviated experimental AR. Abstract : Assessment of IL‐10, CD22 and CD9 in peripheral B10 cells, peripheral blood mononuclear cells (PBMCs) were isolated from blood samples collected from AR patients ( n  = 30) and healthy control (HC) subjects ( n  = 30), and analysed by flow cytometry (FCM). a, CD19 + B cells were gated from PBMCs. b, Gated FCM plots show CD22 + CD9 + B cell counts. c, Boxplots show CD22 + CD9 + B cell frequency in panel (b). d, e, Boxplots show MFI levels of CD9 (d) and CD22 (e) in B10 cells. f, gated FCM plots show IL‐10 + B cell (B10 cells) counts in CD22 + CD9 + B cells in panel (b). g, boxplots show B10 cell frequency of panel (f). h, boxplots show IL‐10 MFI in B10 cells of panel (f). i, j, Protein extracts of B10 cells were prepared, from which IL‐10 levels were determined by Western blotting (i) and ELISA (j). k, l, correlation between IL‐10 MFI and CD22 MFI (k), or CD9 MFI (l). Data in boxplots are presented as median (IQR). ***p < 0.001 (Mann–Whitney test), compared with the HC group. The data in boxplots are presented as median (IQR). Each dot in boxplots presents data obtained from one sample